منتخب کتب سیرہ میں حقوق انبیاء کی کیفیات اور ان کے اطلاقات : تحقیقی مطالعہ: Contemporary Manifestations of the Rights of Prophet Muhammad (PBUH) in Light of Al-Shifa by Qadi Iyad: An Analytical and Research Study - Adnan; Muhammad Subhan (International Research Journal of Arabic and Islamic Studies, 2024)
In the present era, the promotion of the rights of Prophet Muhammad (peace be upon him), also known as Mustafa, is imperative for fostering understanding, tolerance, and peace. Drawing inspiration from Kitab al-Shifa, a renowned Islamic text, practical examples abound in various aspects of contemporary society. One significant avenue is the dissemination of Prophet Muhammad's teachings through modern communication channels. Utilizing social media, online platforms, and multimedia resources, Islamic scholars and educators can share the wisdom and ethical principles espoused in Kitab al-Shifa. This approach allows for a wide-reaching impact, engaging diverse audiences and promoting a nuanced understanding of the Prophet's rights. Moreover, the application of Prophet Muhammad's teachings in addressing contemporary social issues showcases the relevance of Kitab al-Shifa. Initiatives that promote justice, equality, and compassion align with the Prophet's principles and contribute to creating a more just and harmonious society. For instance, projects focused on poverty alleviation, human rights advocacy, and environmental stewardship reflect the Prophet's concern for the welfare of all beings.In the realm of interfaith dialogue, embracing the Prophet's teachings becomes a bridge for mutual understanding. Engaging in respectful conversations and collaborative efforts with individuals of different faiths fosters a spirit of tolerance and unity. Kitab al-Shifa serves as a guide for promoting dialogue that transcends religious boundaries and nurtures a shared commitment to peace Additionally, educational programs that integrate the Prophet's teachings into curricula contribute to shaping ethical and compassionate individuals. By instilling values such as honesty, integrity, and empathy, these programs embody the essence of Kitab al-Shifa and cultivate a generation attuned to the principles of justice and kindness.